The effect of tin prefiltration on extremity cone-beam CT imaging with a twin robotic X-ray system. Issue 2 (May 2022) - Luetkens, K.S.; Huflage, H.; Kunz, A.S.; Ritschl, L.; Herbst, M.; Kappler, S.; Ergün, S.; Goertz, L.; Pennig, L.; Bley, T.A.; Gassenmaier, T.; Grunz, J.-P.
Abstract: Introduction: While tin prefiltration is established in various CT applications, its value in extremity cone-beam CT relative to optimized spectra has not been thoroughly assessed thus far. This study aims to investigate the effect of tin filters in extremity cone-beam CT with a twin-robotic X-ray system. Methods: Wrist, elbow and ankle joints of two cadaveric specimens were examined in a laboratory setup with different combinations of prefiltration (copper, tin), tube voltage and current–time product. Image quality was assessed subjectively by five radiologists with Fleiss' kappa being computed to measure interrater agreement. To provide a semiquantitative criterion for image quality, contrast-to-noise ratios (CNR) were compared for standardized regions of interest. Volume CT dose indices were calculated for a 16 cm polymethylmethacrylate phantom. Results: Radiation dose ranged from 17.4 mGy in the clinical standard protocol without tin filter to as low as 0.7 mGy with tin prefiltration. Image quality ratings and CNR for tin-filtered scans with 100 kV were lower than for 80 kV studies with copper prefiltration despite higher dose (11.2 and 5.6 vs. 4.5 mGy; p < 0.001). No difference was ascertained between 100 kV scans with tin filtration and 60 kV copper-filtered scans with 75% dose reduction (subjective: p = 0.101; CNR: p = 0.706). Fleiss' kappa of 0.597 (95% confidence interval 0.567–0.626; p < 0.001) indicated moderate interrater agreement. Conclusion: Considerable dose reduction is feasible with tin prefiltration, however, the twin-robotic X-ray system's low-dose potential for extremity 3D imaging is maximized with a dedicated low-kilovolt scan protocol in situations without extensive beam-hardening artifacts. Implications for practice: Low-kilovolt imaging with copper prefiltration provides a superior trade-off between dose reduction and image quality compared to tin-filtered cone-beam CT scan protocols with higher tube voltage.